2015
DOI: 10.1155/2015/738608
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects ofTinospora crispaStem Extract on Renal Damage and Hemolysis duringPlasmodium bergheiInfection in Mice

Abstract: Renal damage and hemolysis induced by malaria are associated with mortality in adult patients. It has been speculated that oxidative stress condition induced by malaria infection is involved in its pathology. Thus, we aimed to investigate the protective effects of Tinospora crispa stem extract on renal damage and hemolysis during Plasmodium berghei infection. T. crispa stem extract was prepared using hot water method and used for oral treatment in mice. Groups of ICR mice were infected with 1 × 107 parasitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…The observed potential therapeutic effect of the extracts on liver enzyme activity could be attributed to parasite elimination and/or antioxidant effects of the plant extracts, which could be derived from its bioactive constituents (Gomes et al, 2011;Nutham et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The observed potential therapeutic effect of the extracts on liver enzyme activity could be attributed to parasite elimination and/or antioxidant effects of the plant extracts, which could be derived from its bioactive constituents (Gomes et al, 2011;Nutham et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For extraction, the powdered plant material was extracted with distilled water at the ratio of 1 : 10 using a microwave-assisted method [10, 11] and incubated at room temperature for 3 consecutive days with occasional stirring. After that, filtration was carried out with the Whatman no.…”
Section: Methodsmentioning
confidence: 99%
“…to mice, showed signs of behavioral toxicity. They also reported that the aqueous extract at the dose of 500 mg/kg exerted a hepatoprotective effect during Plasmodium berghei infection in mice [10]. However, in another study, the ethanolic extract of the dried stems of T. crispa (100 and 200 mg/ kg/day for 8 wk oral) was shown to potentiate thioacetamide-induced hepatotoxicity [15].…”
Section: Introductionmentioning
confidence: 97%
“…The stems have been reported to possess antidiabetic activity [7][8][9], while its traditional use encompasses treatment of a wide spectrum of medical conditions. Although there are several reports that endorse the medicinal significance of T. crispa [10][11][12][13], several preclinical and clinical reports illustrate its toxicity. While no reports exist on the LD 50 of T. crispa in laboratory animals, the crude extract of T. crispa has been studied for its hepatotoxic potential in rats and mice.…”
Section: Introductionmentioning
confidence: 99%